Cyber Religion dan Respons Keberagamaan Generasi Milenial di Media Sosial @Bimbingan_Islam - Hendra Hardiyan Syah, Yoshy; Aripudin, Acep; Kuswana, Dadang (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LP2M) Sekolah Tinggi Agama Islam Miftahul Ula (STAIM) Kabupaten Nganjuk, Indonesia., 2025)
This article discusses the practice of religion in cyberspace and the response of the millennial generation to the social media account @Bimbingan_Islam, as a form of practice of Cyber Religion. The purpose of this study is First, to find out how the world of Cyber Religion is on the YouTube, Instagram, and Facebook platforms @Bimbingan_Islam. Second, to find out how the millennial generation responds in the comments column to posts on religious studies on the Instagram platform account @Bimbingan_Islam. This article uses qualitative research methods using data collection techniques (Literature Review) with a non-participatory virtual ethnographic approach and analysis techniques using Lasswell's communication theory. The limitations of the millennial generation referred to in this article are in the age range of 18 to 34 years. What's interesting in this article is that it displays technological developments, illustrations of information dissemination, the level of popularity of social media, and the spread of religious studies in cyberspace, making it a powerful attraction for the millennial generation to continue to deepen, upgrade, and hone their insights about religion, namely on account @ Bimbingan_Islam, then this article finds a case on the social media account, namely there is a sentence that is inappropriate to be presented to the public by using strong language in broadcasting religious studies through social media.